The Usage of E-Learning of Academic Information System (SIAT) as Communication Media for Lecturer and Students at State University of Gorontalo - Wandi Iswanto Nalole; Zulaeha Laisa; Citra Dano Putri (AIBPM Publisher, 2018)
The progress of information and communication in the global era has encompassed almost every aspect of human life. especially in academic life, currently many have made innovation for effective e-learning. the objective of this research is to find out the usage of e-learning in siat as communication media for students and lecturer at state university of gorontalo. this research uses qualitative method and data are collected using observation, interview, and documentation. the observation was conducted to directly see the activity of the research informents, interview to collect the data from the informant, and document analysis as additional data. the research reveals that (1) e-learning media at state university of gorontalo is used to transmit message from lecturer to students. (2) through e-learning in siat, communication between lecturer and students is one way and two ways communication, the message consist of message/instruction from lecturer to students and message to open up discussion space among students and lecturer. Keywords: e-learning, communication, lecturer, students